A Case Study in Making Ocean Education Accessible for Students with Special Needs. Issue 2 (18th September 2020) - Clarke, Lauren; Kast, Dieuwertje J.
Ocean education and ocean-based experiences need to be more inclusive, not only for underrepresented minority students but also for students with special needs. To increase the accessibility of marine science to students in special education, the Young Scientists Program (YSP) hosted an interactive marine science workshop for students in special education classes. During the workshop, students were able to learn the fundamental principles of engineering and engage with the engineering design process by building underwater robots and testing them in an inflatable pool. They were also able to see buoyancy acting on a Cartesian diver while learning about the inverse relationship between the volume and pressure of a gas. The success of this workshop not only demonstrates the positive impact engaging learning experiences have on students in special education but also argues for the inclusion of students with special needs in STEM programs.